Challenges to Online Medical Education during the Covid-19 Pandemic in Medical Colleges of Pakistan - Qudsia Umaira Khan, Hamyel Tahir, Muallah, Danyal Faisal, Aalia Zafar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background The Covid-19 pandemic have forced the education sector of every country to adopt a relatively unconventional method of teaching i.e., Online Education. However, it faces many challenges of its own. Aim: To discuss the challenges to online medical education during the Covid-19 pandemic in medical colleges of Lahore, Pakistan. Methods: A cross-sectional type of quantitative study using a self-administered online questionnaire using Google Forms® was administered to 508 students from all the medical colleges of Pakistan. Results: Majority of subjects preferred face-to-face learning (70.9%) before Covid-19 pandemic and had beginner level online exposure (60. 6%). Overall, 85.8% of participants found the impact of shifting to online learning as negative. A variety of challenges were faced by the students with decreased attention span being most common followed by strain on mental health, problem in communication and taking exams. Conclusion: Covid-19 related lockdown led to new culture of education. Medical students had difficulty adapting to this but a faction of student wanted to use and discover online learning more.